2000
DOI: 10.1046/j.1432-1327.2000.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of L‐carnitine transport into rat skeletal muscle plasma membrane vesicles

Abstract: Transport of l-carnitine into skeletal muscle was investigated using rat sarcolemmal membrane vesicles. In the presence of an inwardly directed sodium chloride gradient, l-carnitine transport showed a clear overshoot. The uptake of l-carnitine was increased, when vesicles were preloaded with potassium. When sodium was replaced by lithium or cesium, and chloride by nitrate or thiocyanate, transport activities were not different from in the presence of sodium chloride. However, l-carnitine transport was clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Although by RT-PCR OCTN1 and -2 were expressed in skeletal muscle, we failed to detect the signals of them by Western blot analysis (data not shown). Recently, similar but differential characteristics of carnitine transport from OCTN2 was reported by using isolated membrane vesicles in rat skeletal muscle, suggesting that OCTN1 or others distinct from OCTN2 participate in muscle in rats (40). Therefore, since human OCTN2 is strongly expressed in skeletal muscle (9), mouse and rat may have different regulatory mechanisms of carnitine disposition from human in terms of carnitine transport in skeletal muscle.…”
Section: Discussionmentioning
confidence: 67%
“…Although by RT-PCR OCTN1 and -2 were expressed in skeletal muscle, we failed to detect the signals of them by Western blot analysis (data not shown). Recently, similar but differential characteristics of carnitine transport from OCTN2 was reported by using isolated membrane vesicles in rat skeletal muscle, suggesting that OCTN1 or others distinct from OCTN2 participate in muscle in rats (40). Therefore, since human OCTN2 is strongly expressed in skeletal muscle (9), mouse and rat may have different regulatory mechanisms of carnitine disposition from human in terms of carnitine transport in skeletal muscle.…”
Section: Discussionmentioning
confidence: 67%
“…It is well established that the sodium-dependent carnitine carrier OCTN2 is expressed in skeletal muscle (Nezu et al, 1999;Spaniol et al, 2001;Stephens et al, 2006;Tamai et al, 1998;Tamai et al, 2000). On the other hand, the study of Berardi et al (Berardi et al, 2000) using rat skeletal muscle membrane vesicles revealed carnitine transport characteristics which are not completely compatible with the properties of OCTN2. It is therefore currently unclear whether the transport of carnitine into skeletal muscle can fully be explained by OCTN2 or whether additional carnitine carriers exist.…”
Section: Discussionmentioning
confidence: 98%
“…acetylcarnitine or propionylcarnitine, on the skeletal muscle carnitine content and physical performance. Elevated carnitine plasma concentrations are not necessarily associated with an increase in the skeletal muscle carnitine content due to saturation of the carnitine transport system into skeletal muscle at normal carnitine plasma concentrations (Berardi et al, 2000) and due to a large concentration gradient between plasma and skeletal muscle (Brass, 2000;Friolet et al, 1994). In comparison to carnitine, skeletal muscle concentrations of acetylcarnitine and propionylcarnitine are much lower under resting conditions.…”
Section: Introductionmentioning
confidence: 96%
“…As shown by Brass et al [23], intravenous administration of a single dose of Lcarnitine is not associated with an increase in the carnitine skeletal muscle content in humans. This can be explained by the observation that carnitine transport into skeletal muscle is saturated at normal carnitine plasma concentrations [26]. On the other hand, long-term administration of L-carnitine over months has been shown to improve physical performance and to be associated with a trophic effect on skeletal muscle in patients on long-term hemodialysis [27,28] or suffering from peripheral arterial disease [29].…”
Section: L-carnitine and Physical Performancementioning
confidence: 99%